THE INFLUENCE OF RUPIAH EXCHANGE RATE ON STOCK PRICES AT PT MUSTIKA RATU TBK - Nurwita; Windy Gustia Wardani (Journal of Business, Management, & Accounting, 2021)
: The purpose of this study was to determine the effect of Rupiah Exchange Rate on Stock Prices at PT Mustika Ratu. This research method is a descriptive quantitative from Time Series. The sampling technique used Purposive sampling technique with a total sample of 13. Data analysis used statistical tools with SPSS version 21 for windows with the an alysis method of normality, coefficient of determination, simple linear regression equations, and hypothesis testing. The result of hypothesis testing shows that the value of T_ (count)> T table Tcount I-2,223 I > Ttable 2,20099. Based on the significance value (Sig),. This means that there is significant effect of the Rupiah Exchange Rate (X2) on the Stock Price (Y).